The Relationship between Sport Specialization and Coping Mechanisms in Adolescent Athletes - Sara Kusner; Laura Harris (Bowling Green State University, 2022)
OBJECTIVE: (1) To describe the coping mechanisms of adolescent athletes as emotion-focused, problem-focused, or avoidant-focused coping before and after injury or illness, and (2) to compare the perceived adolescent coping mechanisms across sport specialization levels (i.e., low, moderate, or high). MAIN OUTCOME MEASUREMENT: Demographic information was reported for the entire sample. A one-way ANOVA was conducted for each dependent variable (i.e., coping strategy) by sport specialization. For the secondary analysis the independent variable time and the dependent variable coping mechanism (i.e., task, emotion, and avoidance) were analyzed by paired t-tests. Hedge's g effect size was calculated for any significant comparisons and alpha was set at 0.05.